The biotechnology of hard coal utilization as a bioprocess substrate - Mutambanengwe, Cecil Clifford Zvandada (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2010)
The development of coal biotechnology, using hard coal as a substrate, has been impeded by its low reactivity in biological processes. As a result, the more successful application studies have focused on lignitic soft coals. However, new studies have reported using biologically or geologically oxidized hard coal as a functional substrate option for bioprocess applications on a large scale. This study undertook a preliminary investigation into the feasibility of environmental applications of coal biotechnology using oxidized hard coal substrates in both anaerobic and aerobic processes with carbon dioxide, sulfate and oxygen as terminal electron acceptors. A preliminary characterization of the oxidized hard coal substrates was undertaken to determine and predict their viability and behavior as electron donors and carbon sources for environmental bioprocess applications of direct interest to the coal mining industry. Both biologically and geologically oxidized coal substrates showed loss of up to 17% and 52% carbon respectively and incorporation of oxygen ranging from 0.9 "“ 24%. The latter substrate showed greater loss of carbon and increased oxygenation. The biologically and geologically oxidized hard coal substrates were shown to partition readily into 23% and 32% organic humic acid, a 0.1% fulvic acid fraction and 65% and 59% inorganic and humin fractions respectively. These organic components were shown to be potentially available for biological consumption. In the unmodified hard coal substrate, partitioning was not observed and it did not perform as a functional substrate for any of the bioprocesses investigated. Where carbon dioxide was used as a terminal electron acceptor, methane production ranging from 9 "“ 26 mg CH4.g substrate-1 was demonstrated from both oxidized coal substrates. Geologically oxidized coal produced 30% more methane than biologically oxidized coal. Methane yields from the geologically oxidized coal in the presence and absence of a co-substrate were 5 "“ 13-fold higher than previous studies that used hard coal for methanogenesis. Based on these results, and that the development and optimization of the biological oxidation process is currently ongoing, further applications investigated in this study were undertaken using geologically oxidized coal. It was shown using pyrolysis gas chromatography mass spectrometry that the methanogenic system was dependent on the presence of an effective co-substrate supporting the breakdown of the complex organic structures within the oxidized hard coal substrate. Also that the accumulation of aromatic intermediate breakdown compounds predominantly including toluene, furfural, styrene and 2-methoxy vinyl phenol appeared to become inhibitory to both methanogenic and sulfidogenic reactions. This was shown to be a more likely cause of reactor failure rather than substrate exhaustion over time. Evidence of a reductive degradation pathway of the complex organic structures within the oxidized hard coal substrates was shown through the production, accumulation and utilization of volatile fatty acids including acetic, formic, propionic, butyric and valeric acids. Comparative analysis of the volatile fatty acids produced in this system showed that geologically oxidized coal produced 20% more of the volatile fatty acids profiled and double the total concentration compared to the biologically oxidized coal. The use of geologically oxidized hard coal as a functional substrate for biological sulfate reduction was demonstrated in the neutralization of a simulated acid mine drainage wastewater in both batch and continuous process operations. Results showed an increase in pH from pH 4.0 to ~ pH 8.0 with sulfide production rates of ~ 86 mgL-1.day-1 in the batch reactions, while the pH increased to pH 9.0 and sulfide production rates of up to 450 mgL-1.day-1 were measured in the continuous process studies using sand and coal up-flow packed bed reactors. Again, the requirement for an effective co-substrate was demonstrated with lactate shown to function as a true co-substrate in this system. However, a low cost alternative to lactate would need to emerge if the process was to function in large-scale commercial environmental treatment applications. In this regard, the aerobic growth and production of Neosartorya fischeri biomass (0.64 g.biomass.g SOC-1) was demonstrated using oxidized hard coal and glutamate as a co-substrate. Both can be produced from wastes generated on coal mines, with the fungal biomass generated in potentially large volumes. Preliminary demonstration of the use of the fungal biomass as a carbon and electron donor source for biological sulfate reduction was shown and thus that this could serve as an effective substrate for anaerobic environmental treatment processes. Based on these findings, an Integrated Coal Bioprocess model was proposed using oxidized hard coal as a substrate for environmental remediation applications on coal mines. In this approach, potential applications included methane recovery from waste coal, use of waste coal in the treatment of acid mine drainage waste waters and the recovery and use of humic acids in the rehabilitation of open cast mining soils. This study provided a first report demonstrating the use of biologically and geologically oxidized hard coals as bioprocess substrates in environmental bioremediation applications. It also provided an indication that follow-up bioengineering studies to investigate scaled-up applications of these findings would be warranted.
Keywords: Coal -- Biotechnology; Acid mine drainage; Coal mines and mining -- Environmental aspects